2015
DOI: 10.1016/j.jaci.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid charge switch defines clinically distinct proline-serine-threonine phosphatase-interacting protein 1 (PSTPIP1)–associated inflammatory diseases

Abstract: Mutations resulting in charge reversal in the y-domain of PSTPIP1 (E→K) and increased interaction with pyrin cause a distinct autoinflammatory disorder defined by clinical and biochemical features not found in patients with PAPA syndrome, indicating a unique genotype-phenotype correlation for mutations in the PSTPIP1 gene. This is the first inborn autoinflammatory syndrome in which inflammation is driven by uncontrolled release of members of the alarmin family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(166 citation statements)
references
References 53 publications
7
158
1
Order By: Relevance
“…The patient exhibited SLE‐like symptoms, including hepatosplenomegaly without typical PAPA syndrome‐like symptoms, such as acne or pyoderma of the skin. The findings in this patient were retrospectively considered somewhat compatible with a diagnosis of Hz/Hc, and the PSTPIP1 p.E250K mutation has also been reported to cause autoinflammatory disease with Hz/Hc …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The patient exhibited SLE‐like symptoms, including hepatosplenomegaly without typical PAPA syndrome‐like symptoms, such as acne or pyoderma of the skin. The findings in this patient were retrospectively considered somewhat compatible with a diagnosis of Hz/Hc, and the PSTPIP1 p.E250K mutation has also been reported to cause autoinflammatory disease with Hz/Hc …”
Section: Discussionsupporting
confidence: 55%
“…The mutation identified in our case, E250K, is typical of PAPA. Patients with hyperzincemia and hypercalprotectinemia (Hz/Hc) have persistent early‐onset inflammatory disease, characterized by cutaneous inflammation, hepatosplenomegaly, failure to thrive, lymphadenopathy, arthritis, neutropenia, anemia, and thrombocytopenia . The patient exhibited SLE‐like symptoms, including hepatosplenomegaly without typical PAPA syndrome‐like symptoms, such as acne or pyoderma of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The name of this disease is not ‘FMF’ or ‘atypical FMF’ despite the fact that there are MEFV mutations—but ‘PAAND’. Similar approach may be applied in the case of PSTPIP1 with the new mutation and different clinical presentation 69. We suggest here a ‘roof’ name: PSTPIP1 -associated AIDs with two subtypes: PAPA and PAMI ( PSTPIP1 -associated myeloid-related proteinaemia inflammatory syndrome).…”
Section: Discussionmentioning
confidence: 94%
“…Holzinger et al 57 found heterozygous mutations in the gene proline/serine/threonine phosphatase interacting protein 1 (PSTPIP1) in patients with the rare syndrome hypercalprotectinemia/hyperzincemia. PSTPIP1 deficiency had been known to cause pyogenic arthritis, pyoderma, and acne (PAPA) syndrome, when mutations disrupt its interaction with inflammatory mediators such as pyrin.…”
Section: Newly Described Primary Immunodeficienciesmentioning
confidence: 99%